2006
DOI: 10.1016/j.jde.2005.07.025
|View full text |Cite
|
Sign up to set email alerts
|

An integro-differential equation arising as a limit of individual cell-based models

Abstract: In this paper, we study mathematical properties of an integro-differential equation that arises as a particular limit case in the study of individual cell-based model. We obtain global wellposedness for some classes of interaction potentials and finite time blow-up for others. The existence of space homogeneous steady states as well as long-time asymptotics for the solutions of the problem is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 16 publications
4
124
0
Order By: Relevance
“…¿From the mathematical point of view aggregation equations have been studied extensively (see e.g. [2], [3], [4], [5], [6], [21], [25] and [36]). In one dimension, in the inviscid case (i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…¿From the mathematical point of view aggregation equations have been studied extensively (see e.g. [2], [3], [4], [5], [6], [21], [25] and [36]). In one dimension, in the inviscid case (i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In one dimension, in the inviscid case (i.e. ν = 0) and for general choices of the kernel K, equation (1.1) has been considered by Bodnar and Velázquez [4]. There by an ODE argument the authors proved the local well-posedness of (1.1) without the diffusion term for C 1 initial data.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…It can be shown that, for suitable choices of V (x), there are many non homogeneous steady states of the Eq. (4.5) for potentials containing an attractive and a repulsive part (see [7]). In some special cases we can give a detailed description of some steady states.…”
Section: Derivation Of the Equations: Potentials With An Attractive Partmentioning
confidence: 99%
“…, n 4 }} on the point p 3,1 , with 1, j = 0. We can further decompose 1, j uniquely into a tangential component 1 1, j in the plane determined by three points p 3,1 , p 3,2 , p 3,3 and a tangential component 2 1, j in the plane determined by three points p 3,1 , p 3,3 , p 3,4 . The magnitude of the perturbation 1 1, j satisfies Eq.…”
Section: Stability Of Clusters In General Space Dimensionsmentioning
confidence: 99%
“…Recently, the finite time blow up problem of (1) has drawn much attention. The existence and uniqueness of solutions for rough initial data and singular potential K has been proven for both one dimension 2,4 and n space dimensions. 20 Finite-time blow-up of solutions under rotationally symmetric kernels with a Lipschitz point at the origin is also known.…”
Section: Introductionmentioning
confidence: 99%